Voltage-dependent inhibition of recombinant NMDA receptor-mediated currents by 5-hydroxytryptamine - Kloda, Anna (2005)
1. The effect of 5-HT and related indolealkylamines on heteromeric recombinant NMDA receptors expressed in Xenopus oocytes was investigated using the two-electrode voltage-clamp recording technique. 2. In the absence of external Mg(2+) ions, 5-HT inhibited NMDA receptor-mediated currents in a concentration-dependent manner. The inhibitory effect of 5-HT was independent of the NR1a and NR2 subunit combination. 3. The inhibition of glutamate-evoked currents by 5-HT was use- and voltage-dependent. The voltage sensitivity of inhibition for NR1a+NR2 subunit combinations by 5-HT was similar, exhibiting an e-fold change per ∼20 mV, indicating that 5-HT binds to a site deep within the membrane electric field. 4. The inhibition of the open NMDA receptor by external Mg(2+) and 5-HT was not additive, suggesting competition between Mg(2+) and 5-HT for a binding site in the NMDA receptor channel. The concentration-dependence curves for 5-HT and 5-methoxytryptamine (5-MeOT) inhibition of NMDA receptor-mediated currents are shifted to the right in the presence of external Mg(2+). 5. The related indolealkylamines inhibited glutamate-evoked currents with the following order of inhibitory potency: 5-MeOT=5-methyltryptamine>tryptamine>7-methyltryptamine>5-HT≫tryptophan=melatonin. 6. Taken together, these data suggest that 5-HT and related compounds can attenuate glutamate-mediated excitatory synaptic responses and may provide a basis for drug treatment of excitoxic neurodegeneration.